Evaluating the intervening factors in patient safety: focusing on hospital nursing staff - Roberta Meneses Oliveira; Ilse Maria Tigre de Arruda Leitao; Leticia Lima Aguiar; Adriana Catarina de Souza Oliveira; Dionisia Mateus Gazos; Lucilane Maria Sales da Silva; Ariane Alves Barros; Renata Lopes Sampaio (SciELO, 2015)
OBJECTIVE To evaluate intervening factors in patient safety, focusing on hospital nursing staff. METHOD The study is descriptive, with qualitative approach, excerpt from a larger study with analytical nature. It was undertaken in a public hospital in Fortaleza, CE, Brazil, between January and June 2013, with semi-structured interviews to 70 nurses, using Thematic Content Analysis. RESULTS The principal intervening factors in patient safety related to hospital nursing staff were staff dimensioning and workload, professional qualification and training, team work, being contracted to the institution, turnover and lack of job security, and bad practice/disruptive behaviors. These aspects severely interfere with the establishment of a safety culture in the hospital analyzed. CONCLUSION It is necessary for managers to invest in nursing staff, so that these workers may be valued as fundamental in the promotion of patient safety, making it possible to develop competences for taking decisions with focus on the improvement of quality care.